2022
DOI: 10.1123/japa.2020-0383
|View full text |Cite
|
Sign up to set email alerts
|

Mahjong Playing and Leisure Physical Activity Alleviate Cognitive Symptoms in Older Community Residents

Abstract: Leisure activities, particularly physically and cognitively stimulating leisure activities, mitigate cognitive decline. The present study aimed to examine the relationship between mahjong playing, leisure physical activity, and mild cognitive impairment (MCI). Older adults with and without MCI were recruited (n = 489, healthy group; and n = 187, MCI group). The regression results showed that years of mahjong playing (odds ratio = 0.595, 95% confidence interval [0.376, 0.961], p = .032) and physical activity (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The theory suggests that participation in cards or mahjong may enhance one’s intellectual and mental activities that are beneficial to better brain function or cognitive function [ 38 ]. Moreover, in addition to enriched emotional and environmental stimulation, playing cards or mahjong requires a certain amount of physical activity in upper extremities, which may increase cerebral blood flow, stimulate the central nervous system excitement, improve brain tissue metabolism, and promote the establishment of brain neural network, therefore resulting in adaptive changes in brain structure and function [ 23 , 39 , 40 ]. Additionally, participation in cards or mahjong also plays an important role in increasing interpersonal communication and social support, reducing psychological stress, thereby mitigating stress-related neuronal changes and improving cognitive function [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The theory suggests that participation in cards or mahjong may enhance one’s intellectual and mental activities that are beneficial to better brain function or cognitive function [ 38 ]. Moreover, in addition to enriched emotional and environmental stimulation, playing cards or mahjong requires a certain amount of physical activity in upper extremities, which may increase cerebral blood flow, stimulate the central nervous system excitement, improve brain tissue metabolism, and promote the establishment of brain neural network, therefore resulting in adaptive changes in brain structure and function [ 23 , 39 , 40 ]. Additionally, participation in cards or mahjong also plays an important role in increasing interpersonal communication and social support, reducing psychological stress, thereby mitigating stress-related neuronal changes and improving cognitive function [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the game requires participants to memorize the titles discarded by others in each round, contributing to memory exercises ( 67 ). Prior research indicates that strategic games can enhance individuals’ logical reasoning skills ( 29 ). Specifically, games like Mahjong, are considered to improve memory accuracy and reaction ability ( 29 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a method to alleviate or delay age-related cognitive decline, it plays a crucial role in effectively mitigating against the inadequate social medical insurance capacity and the scarcity of social medical resources as seen with the aging population in China. For older people, compared to medication therapy for cognitive function improvement, playing Mahjong incurs lower economic costs ( 67 ) and is safer for their physical well-being ( 29 ). Medication therapy often requires longer treatment periods ( 85 ), entails higher expenses ( 86 ), and may not yield satisfactory results ( 87 ), thus exacerbating the economic burden on older adults and posing challenges for long-term medication adherence ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the effects of playing Mahjong on health, particularly on brain function, have been studied ( Table 1 ). Mahjong has been shown to prevent depression in older adults (Tang et al, 2021 ), improve cognitive performance, such as verbal memory in patients with mild dementia (Cheng et al, 2006 , 2014 ; Qiu et al, 2019 ; Zhou et al, 2020 ; Ding et al, 2022 ), and improve higher brain functions, such as increased executive function (Zhang et al, 2020 ). Based on this improvement in executive function, Zang et al concluded that Mahjong improved higher brain function by activating frontal lobe functions, such as concentration and anticipation.…”
Section: Introductionmentioning
confidence: 99%